Prevalence of middle mesial canal and radix entomolaris of mandibular first permanent molars in a western Chinese population: an in vivo cone-beam computed tomographic study - Xin Qiao; Hualing Zhu; Yujia Yan; Jinglin Li; Jiayin Ren; Yuan Gao; Ling Zou (BMC, 2020)
Abstract Background The aim of this study was to investigate the prevalence of the middle mesial canal (MMC) and radix entomolaris (RE) in mandibular first permanent molars in a western Chinese population using cone-beam computed tomography (CBCT). Methods A total of 1174 CBCT images of the mandibular first molars were collected from West China Hospital of Stomatology, Sichuan University. The following information was recorded and evaluated: the detection rate and location of the MMC and RE, the curvature of the RE, the canal configuration and bilateral symmetry. Results The detection rates of the MMC and RE were 3.41 and 25.04%, respectively, as calculated by individuals, and 1.79 and 22.15%, respectively, as calculated by total teeth. The average curvature in the buccolingual (BL) orientation (40.63 ± 14.39°) was significantly larger than that in the mesiodistal (MD) orientation (17.64 ± 7.82°) (p < 0.05). Of 587 patients, 71.72% (421/587) had bilateral symmetry according to the root canal morphology. The prevalence of three-rooted mandibular first molars was higher in males than in females, while the prevalence of two-rooted mandibular first molars was higher in females than in males. Conclusions Our results showed that the RE could be detected in almost 1/4 of the western Chinese population; thus, RE detection requires special attention and careful assessment in endodontic treatment.